The Heavens on Earth : Observatories and Astronomy in Nineteenth-Century Science and Culture - Sibum, Heinz Otto, 1956-; Bigg, Charlotte; Aubin, David, 1967- (Book collections on Project MUSE., 2010)
A cultural history of astronomy in the 19th century that focusses on the issues and perspectives on the role of the observatory in science, society, and culture.